Trabalhadores ribeirinhos do velho chico: experiências, memórias e modos de vida em São Francisco-MG (1980-2011) - Brito, Saulo Jackson de Araújo (2012)
This paper seeks to reflect on the experiences, culture and livelihoods of workers bordering the Old Chico in San Francisco in the north of Minas Gerais. I try to think about the trajectory of these workers, by striking presence on the streets of the city and the importance of these activities, as areieiros, fishermen and vazanteiros. The years between 1980 and 2011 are striking, because in this timeline, I attempt to analyze and understand the experiences, everyday struggles, changes and continuities in the ways of living of these workers. All this historical process lived is marked by important changes in these years, among them we can emphasize the consolidation of the riparian rights of employees, such as the Secure closed season, analyzing the strategies developed by them in an environment marked by strife, conflict, change and permanence of subjects which constitute the search. From the 1990s, the income transfer programs such as Bolsa Família, become of paramount importance and therefore earn dimensions present in the memories produced by workers and, before this transformation process, aware of the impacts of these policies which reorders the present.